2017 Clinical practice guidelines for dyslipidemia of Korean children and adolescents - Lim, Jung Sub (Ann Pediatr Endocrinol Metab, 2020)
The Committee on Dyslipidemia of Korean Pediatric and Adolescents of the Korean Society of Pediatric Endocrinology has newly developed evidence-based clinical practice guidelines for dyslipidemia in Korean children and adolescents. These guidelines were formulated with the Grading of Recommendations, which include both the strength of recommendations and the quality of evidence. In the absence of sufficient evidence, conclusions were based on expert opinion. These guidelines are based on the 2011 National Heart, Lung, and Blood Institute Guidelines, which focus on the prevention of cardiovascular disease in children and draw from a comprehensive review of evidence. These guidelines contain the definition of and screening process for dyslipidemia and introduce new dietary methods: the Cardiovascular Health Integrated Lifestyle Diet (CHILD)-1, the CHILD-2-low-density lipoprotein cholesterol, and the CHILD-2-triglyceride. Potential drug therapies for dyslipidemia along with their main effects and doses were also included.